University Extension and Informal Education: Useful Tools for Bottom-Up Ocean and Coastal Literacy of Primary School Children in Brazil - Stefanelli-Silva, Gabriel; Pardo, Juan C. F.; Paixão, Paulo; Costa, Tânia M. (Frontiers in Marine Science, 2019)
While increasing awareness about ocean-related topics is a matter of urgent necessity, ocean and coastal-literate schoolchildren are uncommon in Brazil, even in coastal cities. In the present study, we report the activities of an environmental education project spanning a 3-year period in São Vicente, a city surrounded by marine habitats in the southeastern state of São Paulo. This project was part of a university initiative aiming to promote shared knowledge between marine biology student-monitors and the encircling community. With the aid of informal and practical educational activities, we introduced topics of marine zoology, marine ecology, waste management and recycling to 200 fifth-year primary students. Using pre- and post-instructional questionnaires, we evaluated the students’ general knowledge of provided ocean and coastal literacy topics. Our results showed a significant difference between initial and final perception across all questions, with a higher questionnaire score after activities. The highest increase in perception concerned lessons on the marine fauna found around the school (94.6% from the initial 7.9%), pointing to the intrinsic value of teaching biological sciences from a zoological perspective. Increased knowledge retention was also observed in lessons on pollution (52.6% from 26.7%), recycling (77.2% from 61.9%), and regional waste treatment (51.8% from 24.2%). Overall, this initiative proved to be a fruitful addition to the school curriculum, especially considering the relevance of rapid urbanization, environmental degradation and water pollution in São Vicente and the role these children might exert as critical-thinking citizens in the future. On the other end, our monitors were also provided with the opportunity for an informal teaching environment complementary to their usual academic-centric degree, with a fresh perspective on accessible scientific communication.